2015
DOI: 10.1093/heapol/czv032
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening capacity to apply health research evidence in policy making: experience from four countries

Abstract: Increasing the use of evidence in policy making means strengthening capacity on both the supply and demand sides of evidence production. However, little experience of strengthening the capacity of policy makers in low- and middle- income countries has been published to date. We describe the experiences of five projects (in Bangladesh, Gambia, India and Nigeria), where collaborative teams of researchers and policy makers/policy influencers worked to strengthen policy maker capacity to increase the use of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
156
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(164 citation statements)
references
References 26 publications
6
156
0
2
Order By: Relevance
“…The results of this study support the observations on gaps by Hawkes et al (2015) in understanding the mechanisms influencing the use of research evidence on policymaking processes and how policymakers can be encouraged to use research evidence. Hardly any resources were directed at capacity development to promote greater use of research evidence in policy makers in this study either.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results of this study support the observations on gaps by Hawkes et al (2015) in understanding the mechanisms influencing the use of research evidence on policymaking processes and how policymakers can be encouraged to use research evidence. Hardly any resources were directed at capacity development to promote greater use of research evidence in policy makers in this study either.…”
Section: Discussionsupporting
confidence: 82%
“…The study also confirmed the conclusions of Hawkes et al (2015) that policymaking processes should be strengthened through organizational capacity building and through data depositories, upgrading of institutional infrastructures and variety of multimedia/social media messages. To increase the capacity to have access to research evidence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In certain contexts, capacity building also seems to have reached a point of decreasing returns (Kislov et al, 2014;Hawkes et al, 2015;Christoplos et al, 2014). There is a risk of building the same individual EIDM skills among the same set of decision makers (easily accessible, national level of government, well-educated, and so on) (NORAD, 2015;Christoplos et al, 2014).…”
Section: Barriers To Effective Capacity Buildingmentioning
confidence: 99%
“…31 Some of the strategies that have been tested in intervention research include providing timely research summaries, training policy makers in critical appraisal skills, deploying knowledge brokers, facilitating proximity and dialogue between policy makers and researchers, and developing packages of interventions that address the culture of policy making settings to make them more evidence attuned. 31,32 Intervention research maintains a focus on study design and methodological rigour, but also embraces challenges of 'natural' context and increasing complexity. This can make it difficult to gain entry into such research, but we argue that it should not deter scholars and advocates for EIPM from embracing key insights from this approach.…”
Section: Critical Theory and Political Philosophymentioning
confidence: 99%